Implications of the O + OH reaction in hydroxyl nightglow modeling - P. J. S. B. Caridade; J.-Z. J. Horta; A. J. C. Varandas (Atmospheric Chemistry and Physics, 2013)
The hydroxyl nightglow has been examined anew using calculated rate constants for the key reactive and inelastic O + OH(v') quenching processes. These constants have been obtained from quasiclassical trajectories run on the adiabatic ab initio-based double many-body expansion-IV potential energy surface for the ground state of the hydroperoxil radical. Significant differences in the vertical profiles of vibrationally excited hydroxyl radicals are obtained relative to the ones predicted by Adler-Golden (1997) when employing an O + OH(v') effective rate constant chosen to be twice the experimental value for quenching of OH(v' = 1). At an altitude of 90 km, such deviations range from ~ 80% for v' = 1 to only a few percent for v' = 9. Other mechanisms reported in the literature have also been utilized, in particular those that loosely yield lower and upper limits in the results, namely sudden-death and collisional cascade. Finally, the validity of the steady-state hypothesis is analysed through comparison with results obtained via numerical integration of the master equations.